Systematic positive expected returns in the UK fixed odds betting market: An analysis of the Fink Tank predictions - Babatunde Buraimo; David Peel; Rob Simmons (International Journal of Financial Studies, 2013)
We report striking evidence of semi-strong inefficiency in the UK fixed-odds football betting market using a reputable newspaper tipster which offers probabilities of match outcomes rather than simple result indicators. Betting on the Fink Tank probabilities of home wins across 10 bookmakers, when there are positive expected returns, would have generated positive returns in each of the seasons from 2006-07 to 2011-12 for a variety of different betting strategies. These returns could have been enhanced by employing the best odds from a greater number of bookmakers. However, the fact that pure arbitrage bets have existed for years and appear to last for several hours or days suggest they are in practice not exploitable to a magnitude that poses any threat to bookmakers.
Keywords: L83; 330; inefficiency; football betting; fixed odds; Fink Tank